ANALISIS MOTIVASI PENGGUNAAN DOMPET DIGITAL OVO PADA MASYARAKAT DI DAERAH ISTIMEWA YOGYAKARTA - Herdioko, Jonathan; Ni Kadek Dewi Damayanti (Modus, 2023)
This study aims to determine the effect of perceived usefulness (PU), perceived ease of use (PEU), privacy and security (PS), and brand image to see the effects on behavioral intention (BI) and actual system use (ASU) on the use of OVO digital wallets in the community in the special area of Yogyakarta. This study uses a quantitative approach with the interval scale method. The number of samples in this study was 105 community respondents in the Special Region of Yogyakarta. The sampling method uses factor analysis techniques. The results of this study indicate that it has no significant effect, so the hypothesis is rejected. Variable testing using path analysis. Keywords: Perceived Usefulness; Perceived Ease of Use; Privacy and Security; Brand Image; OVO Penelitian ini bertujuan untuk mengetahui pengaruh perceived usefulness (PU), perceived ease of use (PEU), privacy and security (PS), dan brand image (citra merek) untuk melihat efek pada behavioral intention (BI) dan actual system use (ASU) terhadap penggunan dompet digital OVO pada masyarakat di daerah istimewa Yogyakarta. Penelitian saat ini menggunakan pendekatan kuantitatif dengan metode interval scale. Sampel diambil pada masyarakat di Daerah Istimewa Yogyakarta dengan total 105 orang. Hasil dari penelitian ini menghasilkan pengaruh yang signifikan, sehingga hipotesis diterima. Pengujian variabel dengan menggunakan analisis jalur. Kata Kunci: Perceived Usefulness; Perceived Ease of Use; Privacy and Security; Brand Image; OVO